2017
DOI: 10.1177/1745691617706099
|View full text |Cite
|
Sign up to set email alerts
|

A Cultural Psychology of Agency: Morality, Motivation, and Reciprocity

Abstract: We highlight the need to culturally broaden psychological theories of social development in providing an overview of our programs of cross-cultural research on interpersonal morality, motivation, and reciprocity. Our research demonstrates that whereas Americans tend to treat interpersonal morality as a matter of personal choice, Indians tend to treat it as a role-related duty. Furthermore, Americans associate greater satisfaction with acting autonomously than with acting to fulfill social expectations, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…Nevertheless, striking cultural differences exist. Moreover, they seem to emerge most often when personal considerations are in conflict with moral, social‐normative, or interpersonal concerns (Miller & Bersoff, ; Miller, Goyal, & Wice, ). Considering the evidence available to children as they attempt to learn about personal and interpersonal causes of behavior, these beliefs are variable for good reason.…”
Section: Cultural Differences: Resolving Ambiguities Between Personalmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, striking cultural differences exist. Moreover, they seem to emerge most often when personal considerations are in conflict with moral, social‐normative, or interpersonal concerns (Miller & Bersoff, ; Miller, Goyal, & Wice, ). Considering the evidence available to children as they attempt to learn about personal and interpersonal causes of behavior, these beliefs are variable for good reason.…”
Section: Cultural Differences: Resolving Ambiguities Between Personalmentioning
confidence: 99%
“…Thus, they interpret the experience of self‐control as an internal struggle (and this could, over time, be reinforcing the link between desires and willpower). Children in Singapore, China, and Peru may instead interpret their struggle as externally driven by norms or expectations of others, or rather, as some theorists suggest (e.g., Lamm et al, ; Miller et al, , ), through a model of self that aligns internal desires with external expectations…”
Section: Self‐controlmentioning
confidence: 99%
“…However, in Eastern cultures that endorse an interdependent self, the prosocial action is viewed as a normative obligation (Miller, ). Thus, acting or failing to act prosocially is a greater source of personal satisfaction or shame (self‐evaluative emotions) in Western cultures (Miller, Goyal, & Wice, ). In the present study, we found that prosocial actions triggered stronger self‐evaluative emotional reactions in Canadian middle and late adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…From a cultural pscyhological perspective, what I describe as Haitian “other-directedness” can be seen to reflect a relational/interdependent modality of self in which principles of action regulation prioritize external contingencies, and in which persons need to actively adjust their own behaviors to social constraints (Kitayama et al., 2007, p. 142; see also Miller, Goyal, & Wice, 2017). Haitian resistance to the inner self-directed meanings of mindfulness can thus be read as an reflection of their relational modality of self that leads them to prioritize consideration of expectations and needs of others in social situations—a mode of self-regulation that may be considered especially valuable when the sociocultural context itself is characterized by uncertainty, contingency, and precarity—as it often is in Haiti.…”
Section: Deep Culture: Is Mindfulness American?mentioning
confidence: 99%